Sensory quality and chemical composition of meat from lambs fed diets enriched with fish and rapeseed oils, carnosic acid and seleno-compounds. (September 2016) - Jaworska, Danuta; Czauderna, Marian; Przybylski, Wiesław; Rozbicka-Wieczorek, Agnieszka J.
Abstract: The aim of the study was to evaluate longissimus muscle quality in lambs fed diets including fish oil (FO), rapeseed oil (RO), carnosic acid (CA) and seleno-compounds. Lambs were fed one of diets: Group I — the basal diet (BD) with 3% RO; Group II — BD with 2% RO and 1% FO; Group III — BD with 2% RO, 1% FO and 0.1% CA; Group IV — BD with 2% RO, 1% FO, 0.1% CA and 0.35 ppm Se as selenized-yeast; Group V — BD with 2% RO, 1% FO, 0.1% CA and 0.35 ppm Se as selenate. The addition of FO and FO, CA and selenium in the inorganic form was characterized by lowest tenderness and juiciness ( P < 0.05). The lowest concentration of fatty acids (ΣFAs), atherogenic-FAs (A SFA ) and thrombogenic-FAs (T SFA ) in the muscle was found for Group V ( P < 0.05). Experimental diets decreased indexes of A SFA and T SFA in muscle. The lowest ratio ( P < 0.05) of n-6polyunsaturated-FAs to n-3polyunsaturated-FAs was obtained for Group III. Highlights: We study effects of fish oil (FO), carnosic acid (CA) and chemical forms of dietary Se (SeY) and (SeVI) on lamb meat quality. The diet with SeVI reduced atherogenic and thrombogenic fatty acid levels in meat. The diet with SeVI reduced the fatty acid level in meat. The diet with FO, CA and SeVI reduced juiciness, tenderness and overall meat quality. The diet with FO and CA reduced the ratio of n-6PUFA to n-3PUFA in meat.